Hydrochemistry of groundwater suprapermafrost in the Machu Picchu aquifer - Ng Cutipa, Wai Long; Masías Alvarez, Pablo Jorge; Cerpa Cornejo, Luis Moroni; Peña Laureano, Fluquer; Torres Gonzalez, Daniel Enrique; Morales Reyna, María del Carmen; Ramos Palomino, Domingo A. (Scientific Committee on Antarctic Research, 2016)
Machu Picchu Peruvian station is located on King George Island, South Shetland Islands, Antarctic Peninsula. Hydrogeology research were conducted during the austral summer 2015, we took groundwater samples in 7 piezometers for analysis of major and minor components, and dissolved metals. Machu Picchu aquifer is a detrital aquifer and it is composed of glacial, alluvial, marine, fluvial, alluvial fluvial and alluvial glacial deposits. Lithological data in piezometers show that about 3 meters deep, there are 3 horizons (Ng et al., 2015): Horizon H1 (more superficial, permeable and porous soil), Horizon 2 (intermediate, semi-permeable to impermeable) and Horizon 3 (depper horizon, permeable and porous ground where groundwater is stored). Groundwater flow is from South to North. Electrical conductivity in the piezometers are low: 92.45 (PZ-08), 126.1 (PZ-07), 218.0 (PZ-04), 219.2 (PZ-03), 219.6 (PZ-06), 324.4 (PZ-09) and 512.5 uS/cm (PZ-05). Watertypes are mixing: Na-Ca-Cl-SO4 (PZ-08), Ca-Na-SO4-HCO3-Cl (PZ-07), Ca-Na-SO4 (PZ-04), Na-Ca-Mg-SO4-Cl (PZ-03), Ca-Na-SO4-Cl-HCO3 (PZ-06), Na-Ca-Mg-SO4-Cl (PZ-09) and Ca-SO4 (PZ-05). Na and Cl values are related to local recharge by thawing snow. Groundwater has low values of Al, Cu, Sr, He, Li, Mn, Ni and Zn; while values of Sb, As, Be, Bi, Cd, Cr, Sn, Hg, Mo, Ag, Pb, Se, Ti, U y V were below the detection limit.